2014
DOI: 10.1074/jbc.m113.504779
|View full text |Cite
|
Sign up to set email alerts
|

Latrophilins Function as Heterophilic Cell-adhesion Molecules by Binding to Teneurins

Abstract: Background:Latrophilins are large adhesion-type GPCRs that may mediate cell adhesion via heterophilic interactions. Results: Latrophilin-1 binding to teneurins exhibits nanomolar affinity, is regulated by alternative splicing, and mediates intercellular adhesion. Conclusion: Latrophilins are cell-adhesion molecules with multiple trans-synaptic ligands. Significance: Our data support a role for latrophilin in trans-neuronal interactions by binding to multiple heterophilic ligands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
315
3
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 174 publications
(336 citation statements)
references
References 49 publications
17
315
3
1
Order By: Relevance
“…As for LPHN3 mRNA brain expression, its peak was observed immediately after birth, followed by a decrease, similar to LPHN2 mRNA decay pattern. In contrast, real-time quantitative PCR done with mouse brain tissues demonstrated that the expression profile of LPHN3 mRNA mimicked LPHN1 pattern, while LPHN2 behaved differently: both LPHN1 and LPHN3 mRNA levels increased after birth reaching a plateau during the period describing intense synaptogenesis, while LPHN2 mRNA levels underwent a constant decrease (34,37). As the function of LPHN seems tightly linked to the development of neuronal tissue, these data suggest that each LPHN isoform may contribute differently in shaping neuronal networks.…”
Section: Developmental Regulation Of Lphn Expressionmentioning
confidence: 53%
See 3 more Smart Citations
“…As for LPHN3 mRNA brain expression, its peak was observed immediately after birth, followed by a decrease, similar to LPHN2 mRNA decay pattern. In contrast, real-time quantitative PCR done with mouse brain tissues demonstrated that the expression profile of LPHN3 mRNA mimicked LPHN1 pattern, while LPHN2 behaved differently: both LPHN1 and LPHN3 mRNA levels increased after birth reaching a plateau during the period describing intense synaptogenesis, while LPHN2 mRNA levels underwent a constant decrease (34,37). As the function of LPHN seems tightly linked to the development of neuronal tissue, these data suggest that each LPHN isoform may contribute differently in shaping neuronal networks.…”
Section: Developmental Regulation Of Lphn Expressionmentioning
confidence: 53%
“…This conclusion was reached since the lectin-like domain had very low affinity for rhamnose. This suspicion turned out to be supported by interaction of the lectin-like domain with the newly identified TEN (37,47). These ligands will be discussed in the "Latrophilin ligands and associated functions" section.…”
Section: The Ntf the Lectin-like Domainmentioning
confidence: 94%
See 2 more Smart Citations
“…Following the transmembrane domain, many teneurins have furin cleavage sites (20) preceding eight EGF repeats, through which teneurins can dimerize due to free cysteines in repeats 2 and 5 forming interchain disulfide bonds (5,21). The following NHL repeat domain is a predicted ␤-propeller and is responsible for homophilic rather than heterophilic interactions in some teneurins (5,22), although heterophilic interactions have also been observed (23). Interestingly, these interactions can lead to the release of the ECD (11,24).…”
mentioning
confidence: 99%